2013
DOI: 10.1097/opx.0b013e31828ec594
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Versus Ocular Aberrations After Overnight Orthokeratology

Abstract: A greater positive shift in corneal compared with ocular SA on day 7 suggests a negative shift in internal SA, which would be consistent with an increased accommodative response. Lack of any difference on day 1 indicates that this may be an ocular adaptation response toward neutralizing induced positive SA, rather than a direct effect of SA changes on the accommodation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 42 publications
7
57
4
3
Order By: Relevance
“…It helps to understand the visual outcome induced by the corneal remodeling after OK. 8 To the best of our knowledge, this is the first study that has comprehensively evaluated the relationship between the changes in corneal thickness profile and higher-order WAs. Similar findings were reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…It helps to understand the visual outcome induced by the corneal remodeling after OK. 8 To the best of our knowledge, this is the first study that has comprehensively evaluated the relationship between the changes in corneal thickness profile and higher-order WAs. Similar findings were reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…As the corneal shape is altered during orthokeratology treatment, both corneal and ocular aberrations, primarily spherical and comatic aberrations, significantly increase . Hiraoka et al investigated the correlations between ocular aberrations and axial elongation in 55 children (mean age: 10.3 ± 1.4 years) undergoing orthokeratology treatment for one year and showed that children with greater increases in the root‐mean‐square (RMS) error values for spherical, comatic, and total higher‐order aberrations (HOAs) exhibited slower axial eye growth.…”
mentioning
confidence: 99%
“…(Stillitano et al 2008) Berntsen et al (2005 found stability of higher order aberrations throughout a day, after one month of OK wear, with 3mm and 5mm pupil sizes. Gifford et al (2013) demonstrated a greater change in corneal than ocular SA from 1 to 7 nights of OK wear, indicating an internal adaptive negative shift in SA, consistent with an increased accommodative response as shown by Tarrant et al, (2009) …”
Section: Orthokeratology: Effect On Aberrationsmentioning
confidence: 51%
“…(Stillitano et al 2008, Fedtke et al 2017 While the relationship between SA and accommodation response has been debated, , Tarrant et al 2010 generally accommodation brings about a negative shift in SA. Gifford et al (2013) found a reduction in whole-eye positive SA after a week of OK wear in young adult myopes, when in comparison to increasing corneal positive SA, indicated an internal increase in the accommodative response evidenced by an increase in negative SA. A decrease in accommodative response in MFSCL wear could be due to an increasing depth of focus, which Kang et al (2016) found did not change after two weeks of wear in young myopic adults.…”
Section: Accommodation -Convergence Interactionsmentioning
confidence: 97%
See 1 more Smart Citation